Selinexor‐based regimens in patients with multiple myeloma after prior anti‐B‐cell maturation antigen treatment. Issue 4 (30th September 2022) - Baljevic, Muhamed; Gasparetto, Cristina; Schiller, Gary J.; Tuchman, Sascha A.; Callander, Natalie S.; Lentzsch, Suzanne; Monge, Jorge; Kotb, Rami; Bahlis, Nizar J.; White, Darrell; Chen, Christine I.; Sutherland, Heather J.; et al.
Abstract: There is a lack of consensus on therapy sequencing in previously treated multiple myeloma, particularly after anti‐B‐cell maturation antigen (BCMA) therapy. Earlier reports on selinexor (X) regimens demonstrated considerable efficacy in early treatment, and after anti‐BCMA‐targeted chimeric antigen receptor‐T cell therapy. Here, we present data from 11 heavily pretreated patients who predominantly received BCMA‐antibody‐drug conjugate therapy. We observe that X‐containing regimens are potent and achieve durable responses with numerically higher overall response and clinical benefit rates, as well as median progression free survival compared to patients' prior anti‐BCMA therapies, despite being used later in the treatment course. In an area of evolving unmet need, these data reaffirm the efficacy of X‐based regimens following broader anti‐BCMA therapy.